Implementation of Metrology in Supporting The Development of Caping Mendawai Tourism Village During The Covid-19 Pandemic Through A Political Perspective - Fuzy Firda Zhan (International Journal of Education, Vocational and Social Science, 2023)
The Covid-19 pandemic has negatively impacted many aspects of human life, including tourism. Whereas previously the tourism sector was a major contributor to the economy of world countries and absorbed a large workforce, thereby reducing unemployment. Through the use of metrology to support tourism in the Caping Mendawai Tourism Village during the Covid-19 pandemic, this research aims to analyze the role of metrology in supporting Indonesian tourism from a political perspective. A descriptive approach and a qualitative methodology were used in this study. From a political perspective, the research findings revealed a metrology implementation model to support the growth of the Caping Mendawai tourism village during the Covid-19 Pandemic, specifically the cooperation between state actors within it. Tourism can then be revived through the implementation of this which is also supported by digital innovation. Along with the capacity for innovation and adaptation, people are expected to have more than one source of income besides tourism.